Interpretasi Radha’ Dalam Tafsir Al-Munir Karya Wahbah Az-Zuhaili: (Tela’ah Penafsiran dengan Pendekatan Tafsir Fiqhi) - Hakim, Abdul; Ani Nur Afidah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Breastfeeding is considered part of a woman's nature in her sexual role. This research is based on the fact that in contemporary times many women do not want to give breast milk to their children for the reason that they still look beautiful and charming. Therefore, the author considers that there is a need for actualization of the Radha'ah concept. This research concludes that it is important to understand the concept and meaning of Radha'ah for babies through in-depth reflection on the holy text of the Koran. Where the Qur'an contains many answers to problems and decisions for Muslims. In this case, the author emphasizes how the Al-Qur'an explains the concept of Radha'ah in Surah Al-Baqarah verse 223 and the implications that arise from the concept of Radha'ah. The discussion regarding breastfeeding has been raised again by several women activists and is part of an effort to interpret fiqh contextually for women. In Islam, giving breast milk is considered something that must be obtained for babies in order to get good nutrition, as well as the rights and obligations for mothers and fathers in providing breast milk. In writing this, it is hoped that this study will be able to provide insight to all readers regarding Radha'ah. As well as expanding the scientific knowledge about Radha'ah which is quoted from the Al-Qur'an. This type of research uses qualitative research and the research data comes from the library, while the primary source in this research is Al-Munir's interpretation. The method used in the research is a qualitative approach while the type of library research is library research. The data analysis method used in this research is descriptive analysis